Exemplary England : historical inquiry and literary recompense in Pope, Gray, and Richardson - Grant, Sarabeth, 1980- (University of Virginia Press, 2023)
"This book argues that literary genres allow for a more capacious view of eighteenth-century English national identity than overt historical documents, as literature provided authors the freedom to challenge the exemplar model and shift their focus away from the enfranchised privileged few"--